EDUPRENEURSHIP-BASED CAREER GUIDANCE MODULE TO FOSTER JUNIOR HIGH STUDENTS’ ENTREPRENEURIAL INTENTION - Siti Zulaikah; Mudafiatun Isriyah; Nasruliyah Hikmatul Maghfiroh (CV. TOTUS TUUS, 2026)
Indonesia faces a persistent school-to-work mismatch, with youth unemployment remaining high and many junior-secondary students lacking career self-awareness and an entrepreneurial mindset. This study therefore aimed to develop and validate an edupreneur-based career guidance module that strengthens early entrepreneurial interest and career readiness among adolescents. Using a Research & Development design adapted from Borg and Gall, the study progressed through needs analysis, planning, prototype development, expert validation, limited field testing (n = 13), revision, and main field testing (n = 40) at SMP Modern Salsabila Al-Tapaq, Kutai Barat. Data were collected via observations, interviews, expert validation sheets (material and media), and student response questionnaires; quantitative results were analyzed with percentage validity, while qualitative data followed Miles–Huberman procedures. The module achieved strong feasibility: material validity = 80% (valid, minor revision) and media validity = 92% (very valid). In the preliminary trial, the share of students with high entrepreneurial interest increased from 30% to 60% (net +30 percentage points), supported by qualitative evidence of improved self-efficacy and opportunity recognition through reflective and experiential tasks (e.g., local case studies, mini-prototype planning). These findings indicate that contextual, values-integrated edupreneurship embedded in career guidance can foster employability-relevant attitudes and decision-making in early adolescence. Practically, the module offers a low-cost, locally adaptable approach aligned with national priorities on life and work skills, and it can be scaled through brief teacher enablement, community MSME partnerships, and micro-grants for classroom trials. Future research should employ quasi-experimental designs with comparison groups, validated multi-item intention/efficacy scales, and longitudinal follow-ups to test durability and behavioral outcomes (e.g., repeated venture trials, basic revenues, documented customer feedback).